Commenting on research results in applied linguistics and education: a comparative genre-based investigation - Lim, Jason Miin Hwa (Elsevier, 2010)
As university students are frequently given the tasks of writing research reports to fulfil their respective programme requirements, teaching novice writers to present the results of their reports understandably constitutes an essential component of English lessons at tertiary level. While past research has shown that results are consistently commented on in the Discussion section in various disciplines, the degrees to which they are allowed in the Results section may vary across different disciplines and across research reports based on different research methods. Without a detailed investigation into such disciplinary and methodological differences, instructors and supervisors would find it difficult to inform novice writers about the permissibility and necessity to incorporate comments of different categories in the Results section. This mixed-method genre-based study used quantitative and qualitative techniques to (i) identify the extent to which disciplinary and methodological differences have a bearing on the frequencies of comments in the Results sections of research papers in applied linguistics and education, and (ii) investigate the various categories of comments in relation to their prominent linguistic mechanisms. The findings of this study can also help instructors design relevant teaching materials that illustrate how experienced writers link their comments with major categories of research results.